IMPLEMENTASI APLIKASI "SAPA MBAK ITA" DALAM PENINGKATAN PELAYANAN PUBLIK DI KOTA SEMARANG - Alfredo, Tulus -; -, yuwanto - (Journal of Politic and Government Studies, 2025)
"Sapa Mbak Ita" as a public service innovation initiated by the Semarang City Government. This channel is designed to enhance transparency, accountability, and responsiveness in accordance with good governance principles. The research employs a qualitative method, utilizing in-depth interviews involving community members and channel administrators as informants. The results indicate that "Sapa Mbak Ita" has successfully served as an effective complaint platform, especially with its real-time status monitoring features accessible via mobile apps, SMS, Twitter, and WhatsApp. The channel is also integrated with SP4N-LAPOR, adhering to Presidential Regulation Number 76 of 2013. Other advantages include increased public trust in the government due to the transparency offered. However, challenges were also identified, such as the limited digital literacy of certain segments of the population and the need to improve human resource capacity in managing the channel. The study recommends digital education for the public to increase participation in using the complaint channel and intensive training for administrators to enhance responsiveness. With these developments, "Sapa Mbak Ita" can serve as a model for managing inclusive, efficient, and sustainable digital complaint channels, significantly contributing to improving the quality of public services in Indonesia.